2013
DOI: 10.1016/j.jtcvs.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and prognostic factors of pleural mesothelioma after surgical diagnosis and/or pleurodesis

Abstract: Median survival in an unselected population of patients with malignant pleural mesothelioma treated nonsurgically is 12 months. Nonepithelioid histology, older age, abnormal C-reactive protein levels, and leukocytosis are independent predictors of worse survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Extra‐pleural pneumonectomy preceded by neoadjuvant chemotherapy and followed by hemithorax irradiation has almost been abandoned in routine practice in France . Treatment of advanced MPMs relies primarily on chemotherapy with combination platinum and pemetrexed and, more recently, bevacizumab .…”
Section: Introductionmentioning
confidence: 99%
“…Extra‐pleural pneumonectomy preceded by neoadjuvant chemotherapy and followed by hemithorax irradiation has almost been abandoned in routine practice in France . Treatment of advanced MPMs relies primarily on chemotherapy with combination platinum and pemetrexed and, more recently, bevacizumab .…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Currently, risk factors used for predicting outcomes after surgery for MPM are histologic subtype, lymph node status, resection margin status, and stage. 8,25 However, these factors cannot be determined before major surgery, making them irrelevant to the decision to undergo resection. Therefore, the identification of preoperative prognostic factors is crucial for allowing patients to make informed decisions regarding treatment, and for classifying patients into groups with distinctly different outcomes to evaluate novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple observational studies have reported prognostic factors in mesothelioma, although many were susceptible to selection bias, having been undertaken in selected populations [164][165][166][167][168][169][170][171]. The forthcoming ERS task force statement on mesothelioma contains information on prognostication, and therefore a full summary of the literature is not replicated here.…”
Section: Prognostication In Mesotheliomamentioning
confidence: 99%
“…In brief, certain factors are consistently associated with survival in mesothelioma, i.e. sex, age, epithelioid differentiation, PS and tumour stage [117,157,[164][165][166][167][168][169][170][172][173][174][175][176][177][178][179][180][181]. However, for other factors, including presenting symptoms or quantification of asbestos exposure, the relationship with survival is less clear [163,165,168,173,[182][183][184].…”
Section: Prognostication In Mesotheliomamentioning
confidence: 99%
See 1 more Smart Citation